Advances in proteomics sample preparation and enrichment for phosphorylation and glycosylation analysis - Xie, Zehu; Feng, Quanshou; Zhang, Shun; Yan, Yinghua; Deng, Chunhui; Ding, Chuan‐Fan (Proteomics (Weinheim), 2022)
As the common and significant chemical modifications, post‐translational modifications (PTMs) play a key role in the functional proteome. Affected by the signal interference, low concentration, and insufficient ionization efficiency of impurities, the direct detection of PTMs by mass spectrometry (MS) still faces many challenges. Therefore, sample preparation and enrichment are an indispensable link before MS analysis of PTMs in proteomics. The rapid development of functionalized materials with diverse morphologies and compositions provides an avenue for sample preparation and enrichment for PTMs analysis. In this review, we summarize recent advances in the application of novel functionalized materials in sample preparation for phosphoproteomes and glycoproteomes analysis. In addition, this review specifically discusses the design and preparation of functionalized materials based on different enrichment mechanisms, and proposes research directions and potential challenges for proteomic PTMs research.